Solanum malmeanum, a promising wild relative for potato breeding - Nicolao, Rodrigo; Gaiero, Paola; Castro, Caroline M.; Heiden, Gustavo (Frontiers in Plant Science, 2023)
Crop wild relatives are gaining increasing attention. Their use in plant breeding is essential to broaden the genetic basis of crops as well as to meet industrial demands, for global food security and sustainable production. Solanum malmeanum (Solanum sect. Petota, Solanaceae) is a wild relative of potatoes (S. tuberosum) from Southern South America, occurring in Argentina, Brazil, Paraguay and Uruguay. This wild potato has been largely mistaken for or historically considered as conspecific with S. commersonii. Recently, it was reinstated at the species level. Retrieving information on its traits and applied uses is challenging, because the species name has not always been applied correctly and also because species circumscriptions and morphological criteria applied to recognize it have not been consistent. To overcome these difficulties, we performed a thorough literature reference survey, herbaria specimens’ identification revision and genebank database queries to review and update the information available on this potato wild relative, contributing to an increase in research on it to fully understand and explore its potential for potato breeding. Scarce studies have been carried out concerning its reproductive biology, resistance against pests and diseases as well as tolerance to abiotic stresses and evaluation of quality traits. The scattered information available makes it less represented in genebanks and genetic studies are missing. We compile, update and present available information for S. malmeanum on taxonomy, geographical distribution, ecology, reproductive biology, relationship with its closest relatives, biotic and abiotic stresses resistance and quality traits and discuss ways to overcome sexual barriers of hybridization and future perspectives for its use in potato breeding. As a final remark, we highlight that this species’ potential uses have been neglected and must be unlocked. Thus, further studies on morphological and genetic variability with molecular tools are fundamental for an efficient conservation and applied use of this promising genetic resource.